2021
DOI: 10.1155/2021/3773943
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver and Gold Nanoparticles: Chemical and Green Synthesis Method and Its Toxicity Evaluation against Pathogenic Bacteria Using the ToxTrak Test

Abstract: In the current investigation, silver/gold nanoparticles (NPs) were synthesized using two methods: chemical and biological, and then characterized colloidal solutions of both NPs using UV-Vis, transmission electron microscopy (TEM) and zeta potential analyzers, X-ray powder diffraction (XRD), and energy dispersive X-ray (EDX) as well as the ToxTrak test for in vitro toxicity and antibacterial activity against Gram-positive bacteria (B. subtilis) and Gram-negative bacteria (E. coli). The plasmon peak of chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The same group has also reported the use of Duchesnea indica for the development of Zn-doped CuO NPs (Zn/CuO NPs) exhibiting a spherical morphology. The green synthesized Zn/CuO NP's anticancer ability was widely studied using A-498 cancer cells and normal human epithelial cells at different concentrations (10,20,40,80, and 160 µg/mL). Figure 11 presents the microscopic images of dead cells on tumor cells treated with green-synthesized Zn/CuO NPs with (hematoxylin-eosin) H&E and (Fluorescein isothiocyanate) FITC staining.…”
Section: Results Of Toxicity and Biocompatibility Studies For Green S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The same group has also reported the use of Duchesnea indica for the development of Zn-doped CuO NPs (Zn/CuO NPs) exhibiting a spherical morphology. The green synthesized Zn/CuO NP's anticancer ability was widely studied using A-498 cancer cells and normal human epithelial cells at different concentrations (10,20,40,80, and 160 µg/mL). Figure 11 presents the microscopic images of dead cells on tumor cells treated with green-synthesized Zn/CuO NPs with (hematoxylin-eosin) H&E and (Fluorescein isothiocyanate) FITC staining.…”
Section: Results Of Toxicity and Biocompatibility Studies For Green S...mentioning
confidence: 99%
“…In the field of tissue engineering, the development of metallic and metal oxide NPs has been amplified, especially for their antibacterial properties [9,10].…”
Section: Overview Of the Use Of Nanoparticles In Tissue Engineeringmentioning
confidence: 99%
“…The NP dosage considers both the actual quantity of NPs that are absorbed by a single cell and the initial concentration of NPs in the cells. For in-vitro and in-vivo experimental models, it is crucial to define genuine and pertinent dosage regimes for risk evaluation in public health [68], [69]. By all means, nanotechnologists should study the toxicity of NPs based on actual dosages rather than inflated ones to elicit a biological reaction.…”
Section: Possible Side Effects Of Copper Nanoparticlesmentioning
confidence: 99%
“…The fundamental properties, such as electronic, optical, magnetic, and catalytic properties, are controlled by the size and shape of the nanoparticle. The level of uniformity or dispersity in biologically produced nanoparticles can vary based on the specific biological method, the involved organisms or biological materials, and the process conditions [62,63]. A few studies also reported that biologically synthesized AuNPs might be a suitable alternative in comparison to chemically synthesized AuNPs for coating antimicrobial medicines in the pharmaceutical industry.…”
Section: Antifungal Activity Of Aunps By Agar Well Assay and Their Sc...mentioning
confidence: 99%